Fractured communities : risk, impacts, and protest against hydraulic fracking in U.S. shale regions - Ladd, Anthony E., 1953- (Nature, society, and culture., 2018)
"While environmental disputes and conflicts over fossil fuel extraction have grown in recent years, few issues have been as contentious in the twenty-first century as those surrounding the impacts of unconventional natural gas and oil development using hydraulic drilling and fracturing techniques--more commonly known as "fracking"--Local communities. In Fractured Communities, Anthony E. Ladd and other leading environmental sociologists present a set of crucial case studies analyzing the differential risk perceptions, socio-environmental impacts, and mobilization of citizen protest (or quiescence) surrounding unconventional energy development and hydraulic fracking in a number of key U.S. shale regions. Fractured Communities reveals how this contested terrain is expanding, pushing the issue of fracking into the mainstream of the American political arena"--